Low-Velocity Impact Response of Novel Prepacked Expanded Clay Aggregate Fibrous Concrete Produced with Carbon Nano Tube, Glass Fiber Mesh and Steel Fiber - Avudaiappan-, S (Elsevier Ltd, 2021)
Recent researches reported that expanded clay aggregate in concrete leads to a notable reduction in strength properties. Nevertheless, the impact response of PEAFC comprising expanded clay aggregate (ECA), multi-walled nano-carbon tubes (MWCNT), steel fiber (SF) and glass fiber mesh (GFM) is still unexamined. It is interesting to draw a sound conclusion regarding the impact response of concretes comprising these four materials. Prepacked expanded clay aggregate fibrous concrete (PEAFC) is a novel type of environmentally sustainable concrete. The development process of PEAFC comprises the following two crucial stages. Firstly, the expanded clay aggregate and fiber are prepacked into the framework in the form of a natural skeleton, followed by grout injection. The skeleton is filled with cement grout comprising multi-walled nano-carbon tubes (MWCNT) obtaining a novel PEAFC. This research investigates the impact response of PEAFC through the drop weight impact test. For this study, forty-one PEAFC mixtures were prepared and divided into five groups. The effect of GFM with different layers and diameters inserted between the two concrete layers was accompanied by incorporating 0.2% of MWCNT and 2.5% dosage of SF. All specimens were tested against drop weight impact according to the guidelines of ACI Committee 544. The studied parameters were the compressive strength, number of the impact causing first crack and failure, impact energy at first crack and failure in addition to impact ductility. Additionally, scanning electron microscopy was utilized to assess the cement grout s microstructural features. The results showed that increasing the diameter of the GFM in between the concrete layers covers a larger crack projection area, which better enhances the crack arresting potential and results in higher impact energy. The GFM diameter increase from 50 mm to 150 mm increased the cracking and failure impact numbers by 49 to 60% and 117 to 152%, respectively. The average percentage improvements in cracking and failure impact numbers due to SF were estimated to be 162 and 670%, respectively. Thus, the SF shared 71 to 96% of the total developments in impact resistance of all mixtures compared to the reference mixture. The addition of 0.2% of MWCNT could adequately fill the nano-pores and nano-cracks resulted in a denser cement grout matrix. The steel fiber was found to be the reinforcement type that leads to the highest improvement contribution in the impact resistance of the tested PEAFC. Despite the use of light weight aggregate, the combined action of GFM, MWCNT and SF could enhance the impact strength of PEAFC. The outcome of this research is to deliver benchmark information for further research work on PEAFC under impact loading. © 2021 Elsevier Ltd